PENGARUH BUDAYA KERJA DAN MOTIVASI KERJA TERHADAP KINERJA GURU DI SMA NEGERI 1 LEMPUING KECAMATAN LEMPUING KABUPATEN OGAN KOMERING ILIR - Dewi, Nurhayati; Ahmad, Syarwani; Indrawati, Sri Wahyu (Jurnal Manajemen Pendidikan, 2024)
This research is to determine the influence of work culture and work motivation on teacher performance. Data collection techniques were carried out through observation, documentation studies and distributing questionnaires. The validity test uses construct validity, while the reliability test uses Cronbach's Alpha. The results of this research are: 1) There is a significant influence between work culture and teacher performance at SMA Negeri 1 Lempuing, Lempuing District, Ogan Komering Ilir Regency. The t value = 3.239 is greater than the t table value of 1.671, this shows that Ho is rejected and Ha is accepted, which means that partially the work culture variable has a significant influence on teacher performance at SMA Negeri 1 Lempuing, Lempuing District, OKI Regency; 2) There is a significant influence between work motivation (X2) and teacher performance (Y) at SMA Negeri 1 Lempuing, Lempuing District, OKI Regency. The results of the t test calculation show that; The t value = 3.290 is greater than the t table value of 1.671 with a significance level = 0.002 < (α) 0.05, the t table value is 1.671), this shows that Ho is rejected and Ha is accepted which means that partially the work motivation variable (X2) has a significant influence significant to the performance of teachers (Y) of SMA Negeri 1 Lempuing, Lempuing District, Ogan Komering Ilir Regency